Water-source contributions to barrier lakes and water-rock interactions in the Wudalianchi volcanic area, Northeast China - Junyu Zou; Zefeng Song; Yamin Duan (Water Supply, 2021)
Wudalianchi is a typical continental Cenozoic volcanic group rich in potassic volcanic rocks (Northeast China). Five hydrologically connected barrier lakes (Lakes 5 to 1) and upwelling cold mineral springs occur, forming a complex lake-groundwater system. Clarifying the water-source contributions and the role of water-rock interactions in the hydrological cycling for barrier lakes remains a challenge from scientific and engineering perspectives. In this study, seasonal variations of multiple isotopes were analyzed. δ18O and δD data indicate that the Wudalianchi lakes were mainly fed by mineral springs. The values, however, were greatly influenced by precipitation (rain and snow) and varying evaporation intensities. In contrast, 87Sr/86Sr ratios varied little between seasons (0.70701–0.7079), suggesting similar water-rock interactions through time. Nonetheless, Sr isotopic mixing models suggested that shallow mineral springs generally contributed >50% of the water to lower reaches. In contrast, the upstream wetland contributed >50% to Lake 5 and decreased down-valley (10.3–53.6%). Calculations based on the δ18O and δD Rayleigh fractionation equation suggest that evaporation in upper reaches was higher than the lower reaches. The evaporation in July was generally higher than in October. This study demonstrates the homogenous water-rock interactions and the associated water mixing effects on the terrestrial volcanic area. HIGHLIGHTS 87Sr/86Sr ratios varied little across seasons; δD and δ18O varied significantly.; δD and δ18O values of lakes were impacted by evaporation and precipitation.; Four endmember sources were identified by geochemical and isotopic data.; Shallow mineral springs and wetland water contributed most to lake waters.; Water-rock interaction and water mixing effect were highlighted in terrestrial volcanic area in eastern China.;